Factors influencing utilization of Manoshi delivery centers in urban slums of Dhaka - Rashid, Sarawat; Hashima-e-Nasreen; Akter, Mahmuda (BRAC Research and Evaluation Division (RED), 2019)
BRAC introduced Manoshi - a community-based maternal, neonatal and child health initiative in urban slums of Bangladesh in 2007. Community delivery centers were established to provide appropriate management of delivery and essential newborn care along with referral facilities. A population and facility-based exploratory qualitative study, conducted during November 2007 to January 2008, aimed to identify factors affecting the use of delivery centers. Data were collected through in-depth interviews, focus group discussions, exit interviews, informal discussion with different service providers and non-participant observations. Findings suggest that slum residents preferred delivery centers because of free service, delivery attended by trained birth attendants, and management of complications through referral linkages. Preference of home delivery and essential newborn care were identified as an important factor that hindered the use of delivery centers though delivery at the centers was safer than the delivery at home. Other reasons for not using the delivery centers were preference for family birth attendants, facing no problem at home, and objection from mothers-in-law. The delivery-centre related factors, namely, absence of medical doctors, non availability of drugs and injections and fear for surgery were also found to be factors resisting use of delivery centers. Provision for salary or other incentives for health providers, quality performance, training of health providers on effective management of complications and good client-provider interaction may influence better use of delivery centers and play a significant role to continue Manoshi in urban slums without BRAC support.